2018
DOI: 10.3847/1538-4357/aad4a9
|View full text |Cite
|
Sign up to set email alerts
|

A New Generation of Cool White Dwarf Atmosphere Models. I. Theoretical Framework and Applications to DZ Stars

Abstract: The photospheres of the coolest helium-atmosphere white dwarfs are characterized by fluid-like densities. Under those conditions, standard approximations used in model atmosphere codes are no longer appropriate. Unfortunately, the majority of cool He-rich white dwarfs show no spectral features, giving us no opportunities to put more elaborate models to the test. In the few cases where spectral features are observed (such as in cool DQ or DZ stars), current models completely fail to reproduce the spectroscopic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 82 publications
3
90
0
Order By: Relevance
“…Experimental laboratory tests are being done to determine whether traditional precision experiments in an environment necessarily at lower density and temperature than in a white dwarf star can verify the potentials through measurements of the wings and line core broadening in absorption spectra in the accessible ultraviolet and visible regions. The good fit of spectra of Ross 640 and LP 658-2 acquired with the Faint Object Spectrograph on board the Hubble Space Telescope, which was obtained by Blouin et al (2018), also confirms our opacity data. The spectra reported here are computed with methods that have a long history of validation both in astrophysical and laboratory applications.…”
Section: Resultssupporting
confidence: 86%
“…Experimental laboratory tests are being done to determine whether traditional precision experiments in an environment necessarily at lower density and temperature than in a white dwarf star can verify the potentials through measurements of the wings and line core broadening in absorption spectra in the accessible ultraviolet and visible regions. The good fit of spectra of Ross 640 and LP 658-2 acquired with the Faint Object Spectrograph on board the Hubble Space Telescope, which was obtained by Blouin et al (2018), also confirms our opacity data. The spectra reported here are computed with methods that have a long history of validation both in astrophysical and laboratory applications.…”
Section: Resultssupporting
confidence: 86%
“…8.-SEDs of hydrogen-free atmosphere models with T eff = 4000 K and log g = 8. The circles correspond to the results obtained using the models of Blouin et al (2018) and the squares to those found with the models of Dufour et al (2007). For the later, note how the SED changes when a minute amount of metals is added to the atmosphere.…”
Section: Resultsmentioning
confidence: 94%
“…This density is low enough that many nonideal high- Table 2 and the hydrogen-free model has T eff = 4620 K, log g = 7.93 and log Ca/He = −10.5. density effects (e.g., nonideal ionization equilibrium, Kowalski et al 2007;Blouin et al 2018 andnonideal dissociation equilibrium, Kowalski 2006) are negligible. Nevertheless, the photospheric density is high enough to significantly affect spectral line profiles.…”
Section: Best Fitmentioning
confidence: 99%
“…In particular, we use the same atmosphere and evolutionary models as in GBB19, with the following exception. Here we rely on a new grid of pure helium models computed using the atmosphere code described in Blouin et al (2018). This code includes numerous high-density ef- fects relevant for the modeling of cool helium-rich white dwarfs.…”
Section: The Photometric Techniquementioning
confidence: 99%